Employing the power of the Tooth Fairy or Raton Perez in developing a community-engaged scientific collection of deciduous teeth - Martinez De Pinillos, Marina; Hlusko, Leslea J.; Modesto, Mario; Towle, Ian; Martinon-Torres, María; Moreno-Torres, Chitina; Fernández, Pilar; Martin-Frances, Laura (American Journal of Biological Anthropology, 2024)
[Resumen no disponible]
Keywords: Ratón Pérez; Tooth Fairy